Expansion with transpalatal arch or continuous arch mechanics - Ledra, Ingrid Muller [UNESP]; Gandini, Luiz Gonzaga [UNESP]; Martins, Renato Parsekian [UNESP] (Elsevier B.V., 2020)
Introduction: This study aimed to compare the 3-dimensional force system produced by transpalatal arch (TPA) mechanics with that produced by a continuous arch (CA) on the expansion of maxillary first molars. Methods: A patient's model with 2 molars in 4-mm crossbite had orthodontic appliances bonded to all teeth. The first and the second molars were connected to two 3-dimensional load cells to compare the forces in the transverse and anteroposterior planes (Fx and Fy) and the rotational moments (Mz) produced in both molars by the expanded TPA and by 0.016-in nickel-titanium CA. The data were evaluated using 6 independent t tests, and the net moment at the molar's center of resistance was also calculated. Results: All forces and moments were different at both molars. At the first molar, CA produced Fx of 2.60 N, Fy of -0.08 N, Mz of -5.16 N.mm, and Net Mz of -5.68 N.mm, whereas the TPA produced Fx of 2.87 N, Fy of -0.60 N, Mz of -22.08 N.mm, and Net Mz of -25.09 N.mm. At the second molar, the TPA did not produce significant forces and moments, whereas the CA produced Fx of -1.00 N, Mz of 3.95 N.mm, Fy of -0.84 N, and Net Mz of -0.67 N.mm. Conclusions: Based on our findings in a clinical set up with the specific horseshoe TPA and archwire tested, with the TPA used only on the first molars and the CA used from one second molar to the other, the mechanics produced different expansion forces at the first molar. The TPA produced a larger rotational side effect on the first molar, whereas the CA produced side effects on the second molar.